H2O chemisorption and H2 oxidation on yttria-stabilized zirconia: Density functional theory and temperature-programmed desorption studies - Gorski, Alexandr; Yurkiv, Vitaliy; Starukhin, Dzmitry; Volpp, Hans-Robert (Journal of power sources, 2011)
The mechanism of H2O dissociation as well as the adsorption and oxidation reaction of H2 on yttria-stabilized zirconia (YSZ), commonly used as part of solid oxide fuel cell (SOFC) anodes, was investigated employing temperature-programmed desorption (TPD) spectroscopy and density functional theory (DFT). In agreement with theory the experimental results show that interaction of gaseous H2O with YSZ results in dissociative adsorption leading to strongly bound OH surface species. In the interaction of gaseous H2 with an oxygen-enriched YSZ surface (YSZ+O) similar OH surface species are formed as reaction intermediates in the H2 oxidation. Our experiments showed that in both the H2O/YSZ and the H2/YSZ+O heterogeneous reaction systems noticeable amounts of H2O are “dissolved” in the bulk as interstitial hydrogen and hydroxyl species. The experimental H2O desorption data is used to access the accuracy of the H2/H2O/YSZ adsorption/desorption and surface reaction kinetics data, employed in previous modeling studies of the electrochemical H2 oxidation on Ni-pattern/YSZ model anodes by Vogler et al. [J. Electrochem. Soc., 156 (2009) B663] and Goodwin et al. [J. Electrochem. Soc., 156 (2009) B1004]. Finally a refined experimentally validated H2/H2O/YSZ adsorption/desorption and surface reaction kinetics data set is presented.